2019
DOI: 10.3389/fimmu.2019.02676
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Analysis of B-Cell Allergen Epitopes to Predict Clinical Cross-Reactivity Between Shellfish and Inhalant Invertebrate Allergens

Abstract: Understanding and predicting an individual's clinical cross-reactivity to related allergens is a key to better management, treatment and progression of novel therapeutics for food allergy. In food allergy, clinical cross-reactivity is observed in patients reacting to unexpected allergen sources containing the same allergenic protein or antibody binding patches (epitopes), often resulting in severe allergic reactions. Shellfish allergy affects up to 2% of the world population and persists for life in most patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 59 publications
3
47
0
Order By: Relevance
“…Molecular phylogenetic analyses of TM and AK revealed that allergy inducing mite and insect homologues are closer to shrimp TM and AK than molluscs. This observation is supported by a recent study by Nugraha et al where IgE antibody binding epitopes demonstrated shared protein regions of clinical importance [33]. MLC of German cockroach is found to have a closer evolutionary relationship to the black tiger shrimp and whiteleg shrimp, whilst the MLC belonging to American house dust mite is closely related to MLC of a different subset of crustaceans, including, the north-sea shrimp, kuruma shrimp, and red swamp crayfish.…”
Section: Evolutionary Relationship Of Shellfish Allergens Tm Ak Mlcsupporting
confidence: 60%
See 2 more Smart Citations
“…Molecular phylogenetic analyses of TM and AK revealed that allergy inducing mite and insect homologues are closer to shrimp TM and AK than molluscs. This observation is supported by a recent study by Nugraha et al where IgE antibody binding epitopes demonstrated shared protein regions of clinical importance [33]. MLC of German cockroach is found to have a closer evolutionary relationship to the black tiger shrimp and whiteleg shrimp, whilst the MLC belonging to American house dust mite is closely related to MLC of a different subset of crustaceans, including, the north-sea shrimp, kuruma shrimp, and red swamp crayfish.…”
Section: Evolutionary Relationship Of Shellfish Allergens Tm Ak Mlcsupporting
confidence: 60%
“…The majority of identified allergens (45%) belong to the group of shellfish and mite allergens. This is not surprising as the shellfish group consists of crustacean (shrimp) and molluscs, which are often combined when analysing related allergens [15,33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tropomyosin exhibits a high degree of structural conservation between species 2 . Several studies have shown clinical cross‐reactivity between crustaceans, mollusks, insects, mites, and nematodes is due mainly to shared IgE (B‐cell) epitopes of tropomyosin 3‐5 . However, there is a lack of understanding whether this high degree of structural and sequence conservation among tropomyosins would also lead to cross‐reactive T‐cell epitopes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several studies have shown clinical cross-reactivity between crustaceans, mollusks, insects, mites and nematodes is due mainly to shared IgE (B-cell) epitopes of tropomyosin. [3][4][5] However, there is a lack of understanding whether this high degree of structural and sequence conservation among tropomyosins would also lead to cross-reactive T-cell epitopes. Currently, some T-cell epitopes have only been elucidated for shrimp tropomyosin with little or no data for other allergenic sources, making analysis of T-cell cross-reactivity challenging.…”
Section: Introductionmentioning
confidence: 99%